Youth, pentecostalism, and popular music in Rwanda - Grant, Andrea (The international African library, 2025)
Youth, Pentecostalism, and Popular Music in Rwanda offers fascinating insight into the lived experiences of young people in Rwanda through ethnographic analysis of the ambiguities and ambivalences that have accompanied the country's rapid post-genocide development. Andrea Mariko Grant considers how Pentecostalism and popular music offer urban young people ways to craft themselves and their futures; to imagine alternative ways to 'be' Rwandan and inhabit the city in the post-genocide era. Exploring the idiom of the heart - and efforts to transform it - this book offers a richly nuanced perspective of urban young people's everyday lives, their aspirations and disappointments, at a political moment of both great promise and great constraint. Rather than insist on a resistance-dominance binary, Grant foregrounds the possibilities of agency available to young people, their ability to make 'noise', even when it may lead to devastating consequences.